Pierre Bourdieu and Public Opinion Poll - Yanyongkasemsuk, Rungnapa (Journal of Social Sciences Naresuan University, 2023)
A poll is a survey of people’s opinions on a topic that is popularized by adopting scientific methods approach. However, the public is now questioning whether polls are objective, free of bias, and politically impartial. The objectives of this study are to 1) investigate Pierre Bourdieu’s concept on public opinion Polls 2) research Pierre Bourdieu’s idea on ontology, epistemology and methodology on public opinion, and 3) research polls in Thai society and related problems. By adopting the methodology of political anthropology to use and analyzing via the viewpoints and ideas of Pierre Bourdieu, this research employs a qualitative research method. The result found that Bourdieu emphasized the importance of the functions of poll, preliminary assumptions in opinion poll, methodology used in polling, politics in polls, and including representation of samples. While scientific procedures can logically explain polls, poll was unable to explain the relationship between the context and living environment of respondents to the survey question. They are also questioned about their neutrality, impartiality, and political ties. Polls, on the other hand, can be quite useful if they are performed with care and details.